ANALISIS RASIO KEUANGAN SEBAGAI DASAR PENILAIAN KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nirwana, Anggun; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2022)
This study aims to see and analyze the effect of Current Ratio and Debt to total assets on Return On Assets in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. In generating the level of company profits or profits, one of the indicators used is Return On Assets. used to be able to see whether the company's financial condition is good or not. With a high return on assets, this means that the company's finances are getting better so that it becomes the target of potential investors to invest. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange, namely 14 and using a sample of 10 according to the criteria set in the sample. Data collection techniques are in the form of documentation and use secondary data sources obtained through the website www.idx.id. The data analysis technique used in this research is statistical test with classical assumption test in the form of normality test, multicollinearity, heteroscedasticity test, and autocorrelation test and using multiple linear regression test consisting of t test and F test, and Coefficient of Determination Test (R²) using SPSS version 25. From the results of the study it can be explained thatsimultaneously on the current ratio and Debt to asset ratio tocompany performance